2016
DOI: 10.1038/srep25369
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of ROS1/ALK/c-MET and therapeutic efficacy of cetuximab plus chemotherapy in advanced biliary tract cancer

Abstract: Aberrant expression of ROS1, ALK or c-MET (RAM) is implicated in carcinogenesis and cancer drug resistance. We retrospectively evaluated the effect of RAM expression on outcomes for advanced biliary tract cancer patients, who were treated with gemcitabine plus oxaliplatin (GEMOX), with or without cetuximab, in a randomized phase II trial. RAM expression levels on archived tissue sections were scored using immunohistochemistry (IHC). Of 110 tumors with IHC staining for all three markers, 18 were RAMhigh (IHC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
1
26
1
Order By: Relevance
“…In non‐small‐cell lung cancer, EGFR expression level is predictive of cetuximab benefit; however, for head and neck SCC and colon cancer, even EGFR expression level is not informative in determining if cetuximab will improve patient outcome . Rather, evaluation of downstream signaling components (e.g., members of PI3K pathway) or other receptor tyrosine kinases (e.g., c‐MET, ROS1, ALK) seems to be more informative in predicting efficacy of anti‐EGFR therapy . More work is needed to determine what molecular signatures are indicative of a positive response to anti‐EGFR treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In non‐small‐cell lung cancer, EGFR expression level is predictive of cetuximab benefit; however, for head and neck SCC and colon cancer, even EGFR expression level is not informative in determining if cetuximab will improve patient outcome . Rather, evaluation of downstream signaling components (e.g., members of PI3K pathway) or other receptor tyrosine kinases (e.g., c‐MET, ROS1, ALK) seems to be more informative in predicting efficacy of anti‐EGFR therapy . More work is needed to determine what molecular signatures are indicative of a positive response to anti‐EGFR treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The OS was 7 months [ 117 ]. Also, the combination of GEMOX with cetuximab increases PFS (7.3 vs. 4.9 months) and OS (14.1 vs. 9.6 months) of patients with ICC relative to GEMOX alone [ 118 ]. Moreover, the treatment of cetuximab for patients with CC and GBC showed one (20%) CR, three (60%) PR, and one (20%) SD of five evaluable patients, indicating that cetuximab may be effective chemotherapy for BTC [ 119 ].…”
Section: Egfr Inhibitors and Their Efficacy In Cholangiocarcinomamentioning
confidence: 99%
“…However, there are few data regarding these alterations in biliary tract adenocarcinomas and previous studies reported contradictory results ( Table 1 of the supplementary data) [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. FIG-ROS1 fusions were detected by PCR in 8.7% cholangiocarcinomas [6] and 9.2%, biliary tract carcinomas (exclusively in extrahepatic biliary cholangiocarcinomas and gallbladder carcinomas) [ 7].…”
Section: Introductionmentioning
confidence: 99%